Creating collaborative educational space in conditions of distanсe learning - Чемоданова, Галина; Власенко, Светлана (Pedagogy and Psychology, 2020)
The article is devoted to the problem of organizing the collaborative educational environment in conditions of distance learning. The author gives an essential characteristic of «collaborative environment» concept which is innovative approach in the training of future specialists. Collaboration is considered as cooperation in solution of the common task, taking into account the immersion of participants in a general communicative context. The priority aspects of the creation of collaborative education include the use of the possibilities of communication and educational technologies for structuring educational information, presenting it in various formats, developing methodological guidelines that serve as a kind of support for the successful fulfillment of tasks provided by the discipline program. The collaboration is also considered as a specific form of interaction and cooperation, which can be used both in the face-to-face and in the distance learning model. Undoubtedly, one of the most important promising tasks in the field of pedagogical research will be studying the characteristics of students and teachers’ communication in the network in order to identify conditions that contribute to constructive solution of problems arising in the training process.